Kesiapan Teknologi Informasi Perbankan hadapi Revolusi Industri era 4.0 - Syafie Syafie (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
A Today the development of information technology is very fast, especially now that it is also in the era of the industrial revolution 4.0. Almost all industries, including the banking industry, have begun to implement breakthroughs to face the era of the industrial revolution 4.0. One of the readiness strategies is to make changes to information technology planning based on Enterprise Architecture. The method discussed uses TOGAF (The Open Group Architecture Framework). Where the goal is to develop business architecture, application architecture, information architecture and technology to be able to adapt to the industrial revolution. To carry out the implementation of the architecture, it is necessary to conduct gap analysis and implementation strategies of the architecture that has been carried out. Application system development does not need to be done totally, but there are several application systems that need to be changed. It is hoped that by implementing Enterprise Architecture starting from architectural design, gap analysis to implementation strategies, the banking industry is able to face the industrial revolution era 4.0.